1999
DOI: 10.1086/314543
|View full text |Cite
|
Sign up to set email alerts
|

Oral, Inactivated, Whole Cell EnterotoxigenicEscherichia coliplus Cholera Toxin B Subunit Vaccine: Results of the Initial Evaluation in Children

Abstract: Two randomized, double-blinded trials assessed the safety and immunogenicity of an oral, killed enterotoxigenic Escherichia coli (ETEC) plus cholera toxin B subunit vaccine in Egyptian children. Two doses of vaccine or E. coli K-12 were given 2 weeks apart to 105 6- to 12-year-olds and 97 2- to 5-year-olds. Safety was monitored for 3 days after each dose. Blood was collected before immunization and 7 days after each dose to measure immune responses. Few children reported postdosing symptoms, with no difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 39 publications
(30 reference statements)
6
50
0
Order By: Relevance
“…This recombinant cholera toxin B (rCTB)-CF ETEC vaccine has been shown to be safe and gave rise to significant immunoglobulin A immune responses in the intestine and increased levels of circulating antibody-producing cells in a majority of adult Swedish volunteers (4). The vaccine has also been well tolerated and given rise to mucosal immune responses against the different CFs of the vaccine in 70% to 100% of volunteers of different age groups from 18 months to 45 years in Egypt and Bangladesh (130,134,(169)(170)(171). However, due to an increased frequency of vomiting in the youngest children (6 to 18 months), a reduced dose of the vaccine, i.e., a quarter dose that can be given safely and with retained immunogenicity to Bangladeshi infants, has been identified (129).…”
Section: Inactivated Whole-cell Vaccinesmentioning
confidence: 99%
“…This recombinant cholera toxin B (rCTB)-CF ETEC vaccine has been shown to be safe and gave rise to significant immunoglobulin A immune responses in the intestine and increased levels of circulating antibody-producing cells in a majority of adult Swedish volunteers (4). The vaccine has also been well tolerated and given rise to mucosal immune responses against the different CFs of the vaccine in 70% to 100% of volunteers of different age groups from 18 months to 45 years in Egypt and Bangladesh (130,134,(169)(170)(171). However, due to an increased frequency of vomiting in the youngest children (6 to 18 months), a reduced dose of the vaccine, i.e., a quarter dose that can be given safely and with retained immunogenicity to Bangladeshi infants, has been identified (129).…”
Section: Inactivated Whole-cell Vaccinesmentioning
confidence: 99%
“…In randomized, controlled trials in Egyptian adults, schoolchildren, and preschool children, we found that the ETECrCTB vaccine was well tolerated and efficiently stimulated immunoglobulin A (IgA)-ASC responses to CTB and CF antigens (14,15). In the present study, we assessed the frequency and magnitude of systemic IgA and IgG antibody responses to the vaccine in these same cohorts and examined isotype-specific patterns of response.…”
mentioning
confidence: 92%
“…A formalin-inactivated whole-cell vaccine produced by SBL Vaccin, Stockholm, Sweden, contains a variety of strains with many of the common CFAs and the B subunit of cholera toxin (CT), which is structurally similar to, and gives cross-protection against, ETEC LT. This vaccine was immunogenic in several adult and pediatric populations (1,9,11,17,18,25). In a study of 685 U.S. citizens traveling to Mexico and Guatemala, the vaccine protected against moderate to severe ETEC illness (protective efficacy of 77%, P ϭ a Antibody levels were measured by time-resolved fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…PBMC were isolated from peripheral blood samples by Ficoll-Hypaque gradient centrifugation, and anti-CFA/II-specific IgA and IgG antibody-secreting cells (IgA/IgG-ASCs) were determined by using an enzyme-linked immunospot assay as previously described (1,17). A positive ASC response was defined as a Ն2-fold increase over the baseline (day 0) value when the baseline value was Ն0.5/10 6 PBMC.…”
Section: Methodsmentioning
confidence: 99%